On the translocation of proteins across membranes. - Singer, S J (1987)
Many proteins of intracellular organelles are first synthesized in the cytoplasm and are then specifically transferred across the membranes of the organelles. On the assumption that these transfers all occur by the same basic mechanism, we enumerate the rather stringent requirements that the mechanism must satisfy. A unitary molecular mechanism is then proposed that meets these requirements.